2023
DOI: 10.1001/jamanetworkopen.2023.22299
|View full text |Cite
|
Sign up to set email alerts
|

Use of Natural Language Processing of Patient-Initiated Electronic Health Record Messages to Identify Patients With COVID-19 Infection

Kellen Mermin-Bunnell,
Yuanda Zhu,
Andrew Hornback
et al.

Abstract: ImportanceNatural language processing (NLP) has the potential to enable faster treatment access by reducing clinician response time and improving electronic health record (EHR) efficiency.ObjectiveTo develop an NLP model that can accurately classify patient-initiated EHR messages and triage COVID-19 cases to reduce clinician response time and improve access to antiviral treatment.Design, Setting, and ParticipantsThis retrospective cohort study assessed development of a novel NLP framework to classify patient-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…After the removal of 143 duplicates, the screening process found 13 studies that met our inclusion and exclusion criteria (19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). We identified two additional studies via reference screening (33,34).…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…After the removal of 143 duplicates, the screening process found 13 studies that met our inclusion and exclusion criteria (19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). We identified two additional studies via reference screening (33,34).…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…The eCOV model was used for COVID-19 electronic health records (EHR) messages (32). eCOV’s classification scored a 94% macro F1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently demonstrated the feasibility of using NLP to automatically prioritize urgent patient messages and identify public health trends from the EHR. 14 Although additional studies have also shown the potential of using text search and NLP to analyze and label messages effectively, [15][16][17][18][19] none have explored the value of adding machine learning (ML) to automate message triage through intelligent rerouting. 20 No previously published efforts have used high-level NLP to analyze and intelligently reroute patient messages.…”
Section: Introductionmentioning
confidence: 99%